Educação musical e promoção da saúde: uma proposta de leitura interdisciplinar - Marco Andree Morel Teliz (2012)
Music is believed to perform different roles in human history. The culture of a specific society, the formative context as well as artistic preferences are one of the multiple factors that determine the kind of influence that music training and music listening provide upon each person. Since early ages, different rituals involving music had a special highlight on wide-ranging societies, and their capacity as cultural source was target of several studies for many years. With the neuroscience outbreak and the upcoming researches emphasizing the music practice from a scientific point of view, new music attributes have been analyzed considering Music Education. Music learning shifts its classic and didactic role and gains an important place on science investigations as well as investigations related with cognitive aspects and cerebral plasticity. Furthermore, music training begins to be noted as an important factor in Health Promotion, being part of different Health Promotion Programs. This study embraces several concepts as Music, Music Education and Health Promotion as well as their close relationship. The main goal of this work is to explain the multiple factors that link musical experience and human health quality. Moreover, through several researches quoted in this study, we give some directed examples and explanations about how mental focus capacity, discipline, reasoning, self-confidence, memory capacity and human sensibility are part of the mutable elements that music training can bring for everyone.